PENGARUH LINGKUNGAN KERJA, DUKUNGAN KERJA, DAN KOMPENSASI TERHADAP KOMITMEN ORGANISASI ASTRA HONDA MOTOR - Harnantoko, Fanny Dwiyan; Prayekti, Prayekti; Subiyanto, Didik (STKIP Persada Khatulistiwa Sintang, 2023)
Employee commitment to the company is one guarantee for maintaining the continuity of the company. Employees who have commitment will work optimally with concentration, thought, energy and time and ensure that the tasks carried out are in accordance with the organization's goals. This research aims to determine the influence of work support, empowerment and organizational commitment on employees of ASTRA Honda Motor Gombong City. The population and sample in this research were all ASTRA Honda Motor Gombong City employees, totaling 50 people using saturated samples, data collection methods using questionnaires, analysis techniques using normality tests, multicollinearity tests, heteroscedasticity tests. T test (partial), f test (simultaneous), multiple linear regression test and coefficient of determination (RÂ²). The research results show that the work environment has a positive and significant effect on employee organizational commitment; work support does not have a positive and significant effect on employee Organizational Commitment; the role of costs has a positive and significant effect on employee Organizational Commitment; and the work environment, work support, and rewards simultaneously influence the Organizational Commitment of employees at Astra Honda Motor, Gombong city.